Analisis Sistem Informasi Akuntansi Manajemen Industri Dalam Penerimaan Kas di Kantor Gubernur Sumatera Utara - Nur Hafiz Syafriani; Arnida Wahyuni Lubis (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine the process of industrial management accounting information system in cash receipts at the North Sumatra Governor's Office, Jl. Pangeran Diponegoro No. 30, Madras Hulu, Kec. Medan Polonia, Medan City, North Sumatra, Zip Code 20152. Problem formulation: What are the advantages and disadvantages in the application of information systems. Research objectives: To find out the advantages and disadvantages in the application of accounting information systems regarding cash receipts. The data collection methods used in this study are decision techniques and direct research in the field. Technical analysis used is the description method, which is a method carried out by analyzing those related to cash receipts.